The Death of Patriotism: Wilfre Owen's Dulce et Decorum Est as an Anti-War Manifesto - Ağır, Adnan Barış (Karabük Üniversitesi, 2013)
Being one of the biggest fluctuations in world history, humanity had never seen an event such World War I that so completely convulsed its existing ideals. Collapsing the existing ethos, the war soon showed its potencies in art and aesthetic. It would be unimaginable that poetry stood indifferent to the massive carnage. The poets who witnessed fighting on the front lines inscribed their experiences into their literary lives and used poetry as a medium of opposing war. They shaped their works to criticize threats directed to humanity. With these pecularities, war poetry, an important move towards modern poetry, stands for a geniune disengagement from the previous naturalistic poetry and signals a change in 20th century thinking. Among war poets, Wilfred Owen is an important figure whose works juxtapose the expected and the actual circumstances of war and his best known poem Dulce Et Decorum is probable to be read as an anti-war manifesto.
Keywords: war; patriotism; shell-shock; poetry; anti-war